Reproductive phases coincide with changes in morphology and photosynthetic physiology in an endangered cycad species. Issue 1 (25th April 2023) - Krieg, Christopher P; Gosetti, Sophia; Watkins Jr, James E; Griffith, M Patrick; McCulloh, Katherine A
Abstract : Cycadales is nominally the most endangered plant group on Earth, yet so much of their basic biology remains unknown which limits conservation strategies. We examined how key aspects of plant function may change with reproductive status in a tropical endangered cycad. We found that sterile individuals may have greater light demands relative to fertile individuals, and fertile individuals may have greater nitrogen demands, which may be critical for successful reproductive events in this endangered cycad. Abstract: Cycadales is highly endangered and one of the oldest dioecious gymnosperm lineages, making their reproductive biology highly relevant to conservation efforts and our understanding of the impact of dioecy, yet cycad reproductive ecophysiology is poorly understood. We examined how the costs associated with reproduction may impact basic physiological variation in cycad species. Specifically, we measured traits related to functional morphology and photosynthetic physiology in sterile and fertile staminate plants ('males') of Zamia portoricensis . Light response curves showed that sterile plants had greater light-use efficiency and maximum photosynthetic capacity per area compared with fertile plants. However, fertile and sterile plants exhibited similar respiration rates. We found significantly more nitrogen in leaves of fertile individuals, but similar nitrogen isotope composition and no differences in carbon content between sterile and fertile individuals. Despite having lower leaf-level photosynthetic rates, fertile plants had greater canopy-level photosynthesis than sterile plants, which was achieved by increasing leaf number and total leaf area. Our data suggest that sterile individuals may have greater light demands relative to fertile individuals, and fertile individuals may have greater nitrogen demands, which may be critical for successful reproductive events in staminate plants of the endangered cycad, Z. portoricensis .